On settler colonialism: ideology, violence, and justice - Kirsch, Adam (W.W. Norton & Company, 2024)
A prominent public intellectual tackles one of the most crucial political ideas of our moment. Since Hamas's attack on Israel last October 7, the term "settler colonialism" has become central to public debate in the United States. A concept new to most Americans, but already established and influential in academic circles, settler colonialism is shaping the way many people think about the history of the United States, Israel and Palestine, and a host of political issues. This short book is the first to examine settler colonialism critically for a general readership. By critiquing the most important writers, texts, and ideas in the field, Adam Kirsch shows how the concept emerged in the context of North American and Australian history and how it is being applied to Israel. He examines the sources of its appeal, which, he argues, are spiritual as much as political; how it works to delegitimize nations; and why it has the potential to turn indignation at past injustices into a source of new injustices today. A compact and accessible introduction, rich with historical detail, the book will speak to readers interested in the Middle East, American history, and today's most urgent cultural-political debates